Experimental study of ELM induced fast-ion transport using passive FIDA spectroscopy at the ASDEX Upgrade tokamak. (2nd March 2021) - Jansen van Vuuren, A.; Geiger, B.; Schneider, P.A.; Bogar, K.; Poloskei, P.Zs.; Cathey, A.; Hoelzl, M.; Jacobsen, A.S.; Cavedon, M.; Dux, R.; Upgrade Team, the ASDEX
Abstract: Measurements using a recently installed edge fast-ion D-alpha (FIDA) diagnostic at the ASDEX Upgrade tokamak show a clear effect of edge localised modes (ELMs) on the passive FIDA signals. While a reduction in the passive FIDA emission is observed in the scrape-off layer (SOL) region, measurements close to the last closed flux surface show an increase in signals shortly after ELMs, followed by a decrease. The decrease provides a clear sign of fast-ion losses in the SOL, while the increase can be explained by an enhanced neutral density during ELMs inside the plasma. In addition, small ELMs are observed, which barely change the neutral density and plasma position but still cause significant changes in the passive FIDA signals. A comparison of the measurements with forward modelling shows that 60% to 80% of the fast ions are lost by ELMs outside the last closed flux surface. In addition, a 20% decrease of the fast-ion density in a range up to 4 cm within the last closed flux surface can be inferred. This range agrees well with the latest modelling results of ELMs using the non-linear MHD code JOREK and shows that less than 0.3% of all fast ions are lost by ELMs.